Analysis of User Satisfaction in the Development of ICT Learning Media Using AR-Based Assemblr Edu with the PIECES Framework Method - Zulham Sitorus; Ami Abdul Jabar; Maida Indrayani; Sipra Barutu; Meiarni Situkkir (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study analyzes user satisfaction in the development of Augmented Reality (AR) learning media using the Assemblr Edu application. The method employed is the PIECES Framework, which includes the variables of Performance, Information, Economics, Control and Security, Efficiency, and Service. The sample consists of 30 respondents, including 1 teacher and 29 students from class X TKJ 1 at SMKS Panca Budi Medan. Data were collected through a questionnaire utilizing a Likert scale to measure satisfaction levels. The analysis results indicate that the respondents' satisfaction level is VERY SATISFIED. This research is expected to contribute to the development of AR-based learning media in education, enhance understanding of user satisfaction with the Assemblr Edu application, and encourage the use of similar technologies in other educational institutions.